Anisakis spp. Larvae in Deboned, in-Oil Fillets Made of Anchovies (Engraulis encrasicolus) and Sardines (Sardina pilchardus) Sold in EU Retailers - Smaldone, Giorgio (Animals (Basel), 2020)
SIMPLE SUMMARY: Sardina pilchardus and Engraulis encrasicolus are largely consumed in Europe as fresh or ripened dishes. Their consumption may represent a public health risk in regard to Anisakis allergic reactions and anisakiasis. This study aimed to evaluate the presence of Anisakis spp. larvae in deboned, in-oil anchovy and sardine fillets marketed in the EU. Ninety semipreserved anchovy and sardine products were examined to evaluate the presence and viability of larvae and identify them. Only 30 nonviable anisakid larvae were found, indicating that processing technologies can influence their presence in final products. It is, however, important that visual inspection is performed only by trained people and that the sources of raw materials are considered in the production flow chart. ABSTRACT: Sardina pilchardus and Engraulis encrasicolus are considered the principal target species for commercial fishing in Europe and are widely consumed as semipreserved products. Although they are considered shelf-stable products, if treatment is not correctly applied, their consumption may represent a public health risk in regard to anisakiasis and allergic reactions. Little is known about the prevalence of Anisakis spp. in ripened products. This study aimed to evaluate the presence of Anisakis spp. larvae in deboned, in-oil anchovy and sardine fillets marketed in the EU to assess the influence of processing techniques on the prevalence of larvae. Ninety semipreserved anchovy and sardine products deriving from the Mediterranean Sea or Atlantic Ocean were collected from different EU retailers and examined using chloropeptic digestion to evaluate the presence of larvae and identify them. Thirty nonviable Anisakid larvae—A. pegreffii (30%) and A. simplex (70%)—were found. The frequency of larvae was higher in anchovies (28.8%). The low frequency of parasites found proved that processing technologies can influence the presence of larvae in final products, but it is important that visual inspection is performed only by trained people. The sources of raw materials should be considered in the production flow chart.